2013
DOI: 10.1245/s10434-013-3292-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Inflammation-Based Prognostic Scores in Patients with Resectable Gallbladder Carcinoma

Abstract: GPS is superior to NLR with respect to its prognostic value for patients with GBC after surgery with curative intent. GPS is not only associated with tumor progression but is also an independent marker of poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 44 publications
3
93
0
Order By: Relevance
“…9 Therefore, the identification of novel methods that can effectively inhibit GBC growth and metastasis is needed. Although lncRNAs were initially argued to be spurious transcriptional noise, recent evidence suggests that they may play a major biological role in cellular development and human diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Therefore, the identification of novel methods that can effectively inhibit GBC growth and metastasis is needed. Although lncRNAs were initially argued to be spurious transcriptional noise, recent evidence suggests that they may play a major biological role in cellular development and human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Curative resection is the only cure for this highly lethal malignancy. However, owing to its non-specific symptoms and highly invasive nature, most patients are at an advanced stage when they are diagnosed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has shown the close relationship between blood system-mediated inflammation and GBC [6]. The relative changes of body inflammatory reaction and immune state are closely related to the occurrence and development of tumors, thereby affecting the prognosis of the tumors [7].…”
Section: Introductionmentioning
confidence: 95%
“…Gallbladder cancer (GBC) is the most common biliary tract malignancy and the seventh most common gastrointestinal cancer [1]. The Surveillance, Epidemiology, and End Results (SEER) program estimates the incidence of GBC at 2.5 per 100,000 persons.…”
Section: Introductionmentioning
confidence: 99%